PENGARUH SISTEM INFORMASI PEMASARAN DAN SEGMENTASI PASAR TERHADAP KEPUASAN KONSUMEN PT GROWTH SUMATERA MEDAN - Novita Sari; Thomas Sumarsan Goh; Errie Margery (JURNAL BISNIS KOLEGA, 2020)
Abstract. This research was conducted at PT Growth Sumatera Medan. The purpose of this study was to determine the effect of Marketing Information Systems and Market Segmentation on the Consumer Satisfaction of PT Growth Sumatera Medan.The population and sample in this study were 62 respondents. Data collection techniques are by distributing questionnaires, interviews and documentation studies. Data analysis uses multiple linear regression analysis.The conclusion of the research is that partially that the Marketing Information System has a positive and significant effect on the Consumer Satisfaction of PT Growth Sumatera Medan. Partially, Market Segmentation has a positive and significant influence on PT Growth Sumatra Medan's Consumer Satisfaction. Simultaneously that the Marketing Information System and Market Segmentation has a positive and significant effect on the Consumer Satisfaction of PT Growth Sumatera Medan.Â Keywords: Marketing Information Systems, Market Segmentation, Consumer Satisfaction.